Semaphore AR card: Interactive scout learning media - Nugraha, I Made Bhisma Putra; Darmawiguna, I Gede Mahendra; Subawa, I Gede Bendesa (Jurnal Inovasi Teknologi Pendidikan, 2024)
This development was triggered by issues related to the lack of interest and enthusiasm of students toward Scout extracurriculars, especially in the Semaphore material aspect. This research aims to produce and implement a Scout educational media design based on augmented reality (AR) Cards and evaluate the responses given by students and coaches. This research applies a Research and Development (R&D) method approach by following the ADDIE development model framework. Research subjects included class X students and extracurricular Scout teachers at Vocational High School 2 Singaraja. The final product of this development is an augmented reality application and Card that can be used on smartphone devices that use the Android operating system. The final results of the research showed very positive achievements, with the black box test producing a success rate of 100%. Validity testing by content experts and media experts Semaphore AR Card got a score of 1.00, indicating a very high level of validity. Likewise, an evaluation of users, which includes both students and trainers, using the UEQ assessment, resulted in a rating of "Excellence" in 6 aspects, including attractiveness, clarity, efficiency, accuracy, stimulation, and novelty. The recommendations from this research are expanding use to various school levels as well as user training to ensure effective use and in-depth understanding. Overall, the developed Scout Semaphore AR Card educational media can be considered a learning tool that is suitable for use in carrying out scouting activities.